Nasal Airflow Simulation Of Patient With Septal Deviation And Allergy Rhinitis - Joanne, Lim Zi Fen (Universiti Sains Malaysia, 2017)
This is a research based on numerical simulation a patient’s nasal airflow by using computational fluid dynamic (CFD). The CT scans of patient with both septal deviation and allergy rhinitis is obtained from Advanced Medical and Dental Institute (AMDI) to study the impact of both diseases to human nasal cavity. The three-dimensional (3D) nasal cavity model of the patient is being constructed by using InVeselius 3.0. The 3D nasal model is then being imported to CATIA V5 for modification and finally imported into ANSYS FLUENT for the numerical solution. The results and effects of these two diseases on a patient are being analyzed on geometrical, cross-sectional area, mass flow rate, pressure and velocity magnitude. The cross-sectional area, velocity magnitude and velocity contours for the four main surfaces: vestibule, nasal valve, middle turbinate and nasopharynx are being analyzed and compared with the standardized nasal cavity as well.